Second home mobility, climate impacts and travel modes: Can sustainability obstacles be overcome?. (July 2019) - Næss, Petter; Xue, Jin; Stefansdottir, Harpa; Steffansen, Rasmus; Richardson, Tim
Abstract: Based on a mixed-methods study of Norwegian second home users, this paper addresses travel distances, modes and carbon dioxide emissions from second home mobility, with a particular focus on reasons for choosing relevant modes of transportation to second home areas and while staying there. The questionnaire data show that the climate impacts are particularly high for trips to second homes located abroad, but due to their higher number, mobility when visiting domestic Norwegian second homes is also a sizeable source of CO2 emissions. Qualitative interviews with 18 participants illustrate important reasons why the car is often considered the default mode of travel when going to Norwegian second homes. These findings provide foundations for proposing land use and transport policies to reduce the climate impact of second home mobility.